DIGITALIZATION OF MANAGEMENT TOOLS IN AGRARIAN BUSINESS - Башлай, Сергій; Кулагін, Дмитро (Modern engineering and innovative technologies, 2023)
The paper deals with the methodological principles of digital transformation in view of the possibility of solving existing management problems in the activities of agricultural business entities in order to ensure their competitiveness. Approaches to de